The role of fiscal policy in confronting environmental pollution in Iraq - Amer Omran Kazem Al-Mamouri; Ibtihal Nahi Shaker Almorshedy (Iraqi Journal for Administrative Sciences, 2024)
Interest in the subject of the environment began during the second half of the twentieth century, and the pace of this interest increased rapidly since the holding of the first World Conference on the Environment in 1972 in Stockholm. It is a subject of a multidisciplinary nature: chemistry, biology, law, and economics. Economists were late in involving themselves in the subject of the environment due to the number of Environmental resources (air, water, etc.) are free goods, meaning they are not scarce and therefore they were not considered factors of production, and no return was allocated to them in the production process (except for the rent corresponding to land rent). However, the industrial sector and the spread of factories in all regions of the Earth - to degrees Varying - led to the emergence of pollution and severe damage to the environmental system, such as an increase in the average temperature on Earth, desertification, the appearance of the ozone hole, the continuous decrease in forest area, the extinction of large numbers of plant and animal species, air pollution, and water pollution... This is how development in its narrow sense has led. To cause severe damage to the environment and humans in the end. Thus, the limited presentation of environmental elements emerged and it became necessary to take into account the environmental dimension in the development process. A new concept of development emerged, which is expressed as “sustainable development,” which means development that does not lead to the depletion of resources or the destruction of environmental patterns.